23rd Paleopathology Association European Meeting, August 25-29, 2022. Vilnius, Lithuania - Jankauskas, Rimantas; Piombino-Mascali, Dario (Vilnius University Proceedings, 2022)
Proceedings of the 23rd Paleopathology Association European Meeting, Vilnius, Lithuania, 25-29 August 2022
Keywords: Paleopathology; Archaeology; Biological Anthropology; Medicine